Detection of Enteric Viruses in a Pilot System for Municipal Wastewater Treatment - R. Romero; A. Galindo; O. Díaz Suárez; Z. Rivero; M Bracho; M. Soler; M. Suárez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2014)
A pilot system for treating municipal waste was evaluated to verify its ability to remove viral pathogens. The presence of Adeno vi rus, Calicivirus, Enterovirus and Hepatitis A and E was determined using RT-PCR. The efficiency of coliphages as indicators and the presence of classic bacterial indicators were also investigated. A 100% positivity was obtained for the presence of all viruses at the entrance and exit of the system; therefore, the system was not able to remove them. Coliphages weren't removed by the system, but they were effective as indicators of enteric viral presence in it. Bacterial indicators reduced their number going through the system, but even at the end of the system, coliforms had numbers above the limits dictated by Venezuelan law. There fore, it would be necessary to add additional steps to the system in order to obtain an effluent that meets the laws and to ensure the absence of enteric viruses.